The profitability of green retrofitting the building envelope of commercial buildings in Cape Town - Botha, Jaco (Department of Construction Economics and Management, 2018)
A notion exists that the operational savings stemming from Deep Energy Retrofits are not sufficient to justify its capital outlay. This notion has focused property developers' attention on the construction of new green buildings, rather than optimizing existing building stock. Producing new buildings, while many existing properties are utilized on a sub-optimal level, with low rental income and high vacancies is not only resource inefficient, but also contributes to a much greater carbon footprint. The aim of this research is to establish whether retrofitting is a viable means of optimizing energy consumption in buildings based on investment return. The literature reveals that the façade is the most significant variable in energy optimisation in buildings and concluded that over-cladding strategies are generally the most efficient means to reduce heat transfer and control lighting levels. The research have been conducted by means of a two tiered methodology involving a case study approach, along with an experimental design, which was conducted through a simulation. A hypothetical building, representative of Cape Town's building stock was modeled and a number of façade over-clad strategies simulated to derive the most optimal solution. The simulation is conducted in DOE Energy Plus and COMFEN GUI. Capital cost data was collected and compared to energy cost savings in order to determine payback values. It was found that over-clad strategies may be economically feasible, which delivered payback periods of between 5 and 19 years, depending on the strategy. A partial retrofit, involving only the East and West facades was found to be the most feasible from an investment point of view, where woven mesh screens delivered the best results.